2017
DOI: 10.1021/acs.jpcb.7b00493
|View full text |Cite
|
Sign up to set email alerts
|

Massively Enhanced Electroosmotic Transport in Nanochannels Grafted with End-Charged Polyelectrolyte Brushes

Abstract: We establish that nanochannels grafted with pH-responsive, end-charged polyelectrolyte (PE) brushes demonstrate a massive augmentation in the strength of the electroosmotic (EOS) transport in the presence of an external electric field. This contradicts the existing understanding that the EOS transport is severely retarded in channels grafted with the PE brushes due to the brush-induced enhanced drag force. Our mathematical model, developed on the basis of the fact that the ion concentration polarization (ICP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…This issue is the presence of possible molecular slip that the fluid flow experiences along the PE brushes. The presence of this slip will imply that the brushes are not strictly behaving as rigid solid cylinders, which in turn, coupled with the localization of the EDL body force away from the nanochannel wall, is responsible for the flow enhancement that we observe (both in this paper as well as all our previous papers (Chen & Das 2017;Chen et al 2018;Maheedhara et al 2018a,b;Sachar et al 2019a;Sivasankar et al 2020a,b)). How can one justify the presence of such intermolecular slip along the brushes?…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…This issue is the presence of possible molecular slip that the fluid flow experiences along the PE brushes. The presence of this slip will imply that the brushes are not strictly behaving as rigid solid cylinders, which in turn, coupled with the localization of the EDL body force away from the nanochannel wall, is responsible for the flow enhancement that we observe (both in this paper as well as all our previous papers (Chen & Das 2017;Chen et al 2018;Maheedhara et al 2018a,b;Sachar et al 2019a;Sivasankar et al 2020a,b)). How can one justify the presence of such intermolecular slip along the brushes?…”
Section: Introductionsupporting
confidence: 53%
“…Such reduced fluid flows are considered as a critical advantage of such brush-functionalized nanochannel systems: weak flow strength ensures that the differences in the ionic migration of the different ions, which is the key to several of the above applications, does not get masked by the background advective transport that acts equally on all the different types of ions. Very recently, in a series of papers (Chen & Das 2017;Chen, Sachar & Das 2018;Maheedhara et al 2018a,b;Sachar, Sivasankar & Das 2019a;Sivasankar et al 2020a,b), however, we have established that such brush-induced weakening of flow strength in PE-brush-grafted nanochannels might not always be true. We showed that for certain cases where nanochannels are grafted with end-charged PE brushes (Chen & Das 2017;Chen et al 2018;Maheedhara et al 2018a,b), some particular combination of grafting density, brush properties and salt concentration will lead to significantly enhanced nanofluidic EOS or induced EOS transport.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a recent set of papers, we made the first attempt to describe the ionic and liquid transport in PE brush–grafted nanochannels in a framework that accounts for the PE brush configuration while describing the PE brush EDL electrostatics . In other words, the PE brush EDL electrostatics is obtained by minimizing the free energy of the entire system that also yields the corresponding PE brush configuration.…”
Section: Introductionmentioning
confidence: 99%